A depiction of Don Juan Manuel’s political life from manuscript sources - Pavón Casar, Fátima (Documenta & Instrumenta - Documenta et Instrumenta, 2012)
It’s an analisis of the personality of Don Juan Manuel, not only a remarkable author of Medieval Spanish Literature, but a very important politician, because he played a main role in the kingdom of Castile in the XIV century, specially during the reign of Alfonso XI, as he was his tutor throughout his minority. Besides, her daughter Juana Manuel, Henry of Trastámara’s wife, legitimized this royal dinasty as it was showed clearly with the king John I’s speech, pronounced at the Cortes of Segovia in 1386. We have collected written sources and images from different historical documents and manucripts to document the political importance of the Infante Don Manuel’s son, who was the youngest brother of Alfonso X the Wise.